When a Nudge Backfires: Combining (Im)Plausible Deniability with Social and Economic Incentives to Promote Behavioral Change - Gary E. Bolton; Eugen Dimant; Ulrich Schmidt (Center for Economic Studies and ifo Institute (CESifo), 2020)
Both theory and recent empirical evidence on nudging suggest that observability of behavior acts as an instrument for promoting (discouraging) pro-social (anti-social) behavior. We connect three streams of literature (nudging, social preferences, and social norms) to investigate the universality of these claims. By employing a series of high-powered laboratory and online studies, we report here on an investigation of the questions of when and in what form backfiring occurs, the mechanism behind the backfiring, and how to mitigate it. We find that inequality aversion moderates the effectiveness of such nudges and that increasing the focus on social norms can counteract the backfiring effects of such behavioral interventions. Our results are informative for those who work on nudging and behavioral change, including scholars, company officials, and policy-makers.
Keywords: C91; D64; D90; 330; anti-social behavior; nudge; pro-social behavior; reputation; social norms